Leadership Strategies In Preventing Bullying Behavior Among Students At The Ma’had Tahfidzil Qur’an Foundation Islamic Centre Of North Sumatera Medan - Saniah Salsabila Nasution; Misrah, Misrah (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to determine the forms of bullying that occur among students, the strategies of the school leadership in preventing it, and the inhibiting and supporting factors in implementing these strategies at the Qur'an Tahfidzil Ma'had of the Islamic Center Foundation of North Sumatra, Medan. The study used a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, then analyzed using an interactive model including data reduction, data presentation, and conclusion drawing. The results showed that the dominant form of bullying was verbal bullying, which impacted the psychological well-being of students. Prevention strategies were implemented through delegation of authority to relevant units such as Guidance and Counseling, Student Affairs, and Parenting, as well as the involvement of the student organization (OSIC). Other strategies included early education, routine coaching, parental involvement, and the implementation of educational administrative sanctions. Inhibiting factors included unclear division of duties, minimal reporting by counselors, and structural barriers. Supporting factors included the development of job descriptions in each unit and a more structured reporting system.